Essays on industrialisation, innovation, and sustainable development in Sub-Saharan Africa - Akorsu, Patrick Kwashie (University of the Witwatersrand, Johannesburg, 2023)
Sustainable development has attracted discourses from academics and policymakers for some time now. The United Nations has instituted seventeen (17) goals to promote sustainable development, and these goals have been decomposed into 169 sub-goals to be achieved under the 2030 agenda for sustainable development. The goals are essentially grouped into economic, ecological, and social goals. Following this, the African Union (AU) has embraced the SDGs by motivating member countries to come up with programmes that are directly related to the goals. However, whereas a lot of discussions have occurred, much of the talk has been oblivious to empirical data analysis. The AU has realised the importance of industrialisation in spearheading the bridging of the poverty gap in Africa. Industrialisation is seen as the panacea for job creation, prosperity, and wealth creation. Industrialisation induces innovation by introducing new equipment, new production techniques, increasing capacities and spreading improvements across sectors of the economy. However, since the 1990s when the policymakers started talking about industrialisation, not much has been achieved on that score. Common to industrialisation and economic development is financial development. The level of financial development can stimulate positive or negative externalities on sustainable development. The drive towards the promotion of sustainable development in Africa by the African Union and other parastatal bodies, especially the UN, motivated this thesis to examine the convoluted connections between financial development, technological innovation, industrialisation, and sustainable development in Africa in three related studies. The first study analysed the complementary role of financial development in the relationship between industrialisation and sustainable economic development in Africa. The system dynamic Generalised Method of Moments (GMM) technique was employed with a dataset covering 2010-2019 for 48 African countries. Under this analysis, this thesis found that Industrialisation, Innovation, and Sustainable Development in Africa © Patrick Kwashie Akorsu, 2023 industrialisation is a significant positive driver of economic development. The role of financial development in the economic development agenda among African economies was also emphasised by the results. The outcome of the moderation analysis suggested that the level of financial development significantly complements industrialisation towards improving economic growth. Thus, a more developed financial sector is potent in building an industrial economy which facilitates value addition in the manufacturing sector. The second empirical analysis examined the interactive role of technological innovation in the relationship between financial development and sustainable development in Africa after controlling for the influence of ICT infrastructure, trade openness, inflation, and population size. The results indicated significant effects of financial development on sustainable development as well as significant relationships between technological innovation and sustainable development. In terms of social sustainability, the findings suggested that financial development tends to reduce social sustainability among African economies such that increasing the quantum of broad money and increasing the amount of domestic credit to the private sector either by households or by banks would not necessarily improve the level of social development in Africa. Concerning economic sustainability, the findings divulged a positive relationship between financial development and the economic dimension of sustainable development (i.e., economic sustainability), suggesting that African countries could leverage financial development, particularly by encouraging the supply of credit to the private sector either by households or banks to enable industries to improve their operations. As regards ecological/environmental sustainability, findings from this empirical analysis indicated mixed relationships between financial development and ecological sustainability. Thus, depending on the proxy, financial development either increases or decreases energy consumption and carbon dioxide emissions in Africa. Meanwhile, the effect of technological Industrialisation, Innovation, and Sustainable Development in Africa © Patrick Kwashie Akorsu, 2023 innovation on sustainable development was positive for all dimensions of sustainability but had varied implications. This emphasised the need to analyse how sustainable development is affected by the interaction between financial development and technological innovation. The findings from the moderation effect divulged that more technological innovation lessens SDI but increases GDP growth per capita, carbon dioxide emissions, and energy consumption. The last empirical chapter revealed investigated the interactive role of technological innovation in the relationship between financial development and sustainable development in Africa. The findings from such an analysis highlighted the complementary role of technological innovation in the relationship between financial development and sustainable development in Africa. In an era of an increasing need for sustainability, these findings stressed the need to further ascertain possible convolutions between sustainable development, technological innovation, and industrialisation among African economies. The impetus for this analysis partly stemmed from the fact that industrialisation has some externalities it poses to economies. Therefore, there was a need to provide empirical evidence that helps understand the true role of industrialisation in the relationship between technological innovation and sustainable development to foster policy formulation. Upon analysing the mediating effect of industrialisation on the relationship between technological innovation and the three dimensions of sustainable development (social, economic, and ecological/environmental sustainability) in Africa, positive relationships between technological innovation and all dimensions of sustainable development, emphasise the need to analyse how sustainable development is indirectly affected by industrialisation. The findings provide evidence of a partial contribution from industrialisation toward the impact of technological innovation on sustainable development. As a result, this thesis Industrialisation, Innovation, and Sustainable Development in Africa © Patrick Kwashie Akorsu, 2023 concluded that the level of industrialisation complementarily mediates the relationship between technological innovation and sustainable development in Africa. The study recommends that economies within Africa should focus on industrialisation and financial development to achieve sustainable development. Policymakers should prioritise the development of a resilient financial sector to complement industrialisation, while promoting technological innovation to support all dimensions of sustainability. Also, a balanced approach to sustainable development should be promoted by managing the trade-offs between sustainability dimensions. Finally an effectively coordinated set of policies should be put in place to reduce negative externalities resulting from industrialisation, and policymakers should carefully select implementation policies and channels
A research report submitted in partial fulfillment of the requirements for the Doctor of Philosophy to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Africa; Carbon dioxide emissions; Financial development; General method of moments; Industrialisation; Sustainable development; Technological innovation; UCTD; SDG-9: Industry, innovation and infrastructure